Analisis Postur Kerja pada Stasiun Kerja Proses Som Kaos Kaki Studi Kasus UD. Karunia Sentosa Utama - Muhammad Zainal Arifin, Akh. Sokhibi (Journal of Industrial Engineering and Technology, 2021)
Working long hours on certain job sequences can lead to complaints on the operator like musculoskeletal disorders (MSDs). The UD Karunia Sentosa Utama is a manufacturing company that specializes in sock production. Observation on the UD Karunia Sentosa Utama found that the work station of the som engine section had a narrow, less-ergonomic area for the operator. The study aims to find out how much risk and risk factors an operator might be able to experience at the sock som work station section. Research based on its properties includes quantitative work in which research involves quantifying or quantifying data. Based on an analysis of the Nordic body map (NBM) questionnaires, from the scoring already done the results of a total individual score of 51. Based on the percentage of complaints from histogram processing obtained 39.3% point of no pain found, 39.3% found little pain, and 21.4% found pain. From the final scor for RULA, score was obtained by 6, whether it was from the ergofellow software or from the calculations. 6 the most high-risk points include (occipital, left shoulder, back, waist, hip, buttocks).